Effects of selected process variables on the stability of petroleum emulsions co-stabilized by carbon black and surfactant - Umar, A.A. (Society of Petroleum Engineers, 2017)
Petroleum emulsions formed in the oil industry are pricy problems both in terms of chemicals used and the production lost. These emulsions form when oil and brine come into contact with each other, with the influence of sufficient mixing, and in the presence of surface-active-agents (surfactants) or emulsifiers. Although, these emulsions might not form except in the presence of emulsifiers, the amount of agitation, residence time (ageing), among other variables are very critical to its formation and subsequent stabilization. The emulsions are treated to remove the dispersed water and associated inorganic salts to meet market specifications, transportation requirement and to reduce corrosion and catalyst poisoning in downstream processing. This study aims at investigating the effects of selected process variables; viz-aviz: Residence time, mixing rate, surfactant concentration (span 80)(v/v), and carbon black concentrations (wt) on the stability of petroleum emulsions. Crude oil from an offshore Malaysian oilfield was used as the oleic phase, and distilled water as the dispersed aqueous phase. Sequences of laboratory experiments as designed by the Response Surface Methodology (RSM) were conducted. The RSM helps to optimize the process, influenced by number of operating parameters with a minimum number of experiments as well as to evaluate the interaction between the parameters. Results showed that a Carbon Black (CB) and surfactants provide better and longer stability than either CB particles or Span80 alone. Also, mixing rate (agitation) and aging show direct proportion to stability of the studied emulsions.